2013
DOI: 10.1590/s0103-21002013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes com acidente vascular cerebral em reabilitação

Abstract: Objectives: To evaluate and correlate quality of life and depression of patients in rehabilitation after stoke. Methods: A transversal study conducted in two rehabilitation services with patients after stroke. Information collected included sociodemographic data, the Medical Outcome Study Short-form 36 -item Health Survey, the Stroke Specific Quality of Life Scale, the Barthel Index and the Beck Depression Inventory. Results: The sample consisted of 139 patients, with a mean age of 59.4 years; 59% were male. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 19 publications
4
28
2
25
Order By: Relevance
“…The lack of access to information and health care services can increase the possibility of being ill. Consequently, studies found survivors who earn one minimum wage or less. (6,18) Similarly, most of this study's participants had low income, which is compatible with the fact that the data collection site was exclusive for Unified Health System users.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The lack of access to information and health care services can increase the possibility of being ill. Consequently, studies found survivors who earn one minimum wage or less. (6,18) Similarly, most of this study's participants had low income, which is compatible with the fact that the data collection site was exclusive for Unified Health System users.…”
Section: Discussionsupporting
confidence: 65%
“…(4)(5)(6)13,14) In this study, there was a predominance of brown men and mean age was lower (57.3 years). This may reflect the regional population characteristics.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations